The Role of Job Satisfaction in the Effect of Compensation on Employee Performance - Nirmalasari Nirmalasari; Ratih Amelia (International Journal of Business Economics (IJBE), 2020)
The purpose of this study is to determine the effect of compensation on job satisfaction, to determine the effect of compensation on lecturer performance through job satisfaction. The population and sample in this study were 52 permanent lecturers at the LP3M Superior Polytechnic. Furthermore, the sampling technique uses saturated samples. Then the data collection technique used a questionnaire with a Likert scale. Data analysis using path analysis. Path analysis is used to see the direct and indirect effects of compensation, job satisfaction and performance variables. The results showed that compensation and work discipline had a positive and significant effect on lecturer job satisfaction. Furthermore, the indirect effect shows that the compensation variable has no effect on lecturer performance through job satisfaction.